VD_FINDINFO HC / 2013 / 806 vom 10. Dezember 2013 - VD Tribunal cantonal (2013)
DÉCISION D'IRRECEVABILITÉ, DÉLAI DE RECOURS, INDICATION ERRONÉE DES VOIES DE DROIT | 248 let. e CPC (CH), 321 al. 1 CPC (CH), 321 al. 2 CPC (CH), 321 CPC (CH), 104 CDPJ, 111 CDPJ